Perception of Teachers about Planning of Single National Curriculum in Public and Private Schools at Primary Level in Rawalpindi - Mehmood , Azhar; Ahmed, Dr. Aftab; Younas, Muhammad (ACADEMIA International Journal for Social Sciences, 2025)
The social, political and economical progress of a nation highly depends on its educational system. To achieve its aims and goals a dynamic educational system having sustainable curriculum is imperative for a country, which also reflects its development, prosperity and social structure. To provide equal opportunity, uniform educational achievements to all pupils and to minimize disparities and fragmentation among different social sectors first phase of Single National Curriculum implemented in public and private primary schools by Pakistan in 2021. This study examines and compares the planning of implemented SNC at primary level in public and private schools in District Rawalpindi of Punjab. The planning of SNC was delimited to the three elements of curriculum objectives, content and teaching methods. The quantitative and descriptive approach was utilized to accomplish this study. Through stratified sampling 188 public and 143 private school teachers from heterogeneous population of all primary school teachers of Tehsil Kahuta and Kallar Syedan from District Rawalpindi were selected. A self-developed questionnaire for survey to collect data was utilized. The descriptive mean, standard deviation, frequency and inferential statistics t-test through SPSS were used to compare the planning of SNC. The major findings of the study are that SNC is well planned. It recommends that the next phases of Single National Curriculum may be after improving the content implemented in all schools.